Thromboembolic events associated with the treatment of cerebral aneurysms with Guglielmi detachable coils. - Pelz, D M; Lownie, S P; Fox, A J (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE The purpose of this study was to document the prevalence, radiologic appearance, and treatment of thromboembolic events related to GDC embolization of cerebral aneurysms.METHODS The clinical and radiologic records of all patients undergoing GDC treatment of intracranial aneurysms at our institution were reviewed. All cases in which unexpected complications occurred were selected. Those complications related to presumed thromboembolic events were analyzed.RESULTS Of 59 patients (60 aneurysms) treated with GDCs, 17 (28%) experienced thromboembolic events. Seven patients had transient ischemic attacks and 10 had strokes. In 10 patients, the deficits occurred during or immediately after the procedure; in the rest, the complications were delayed. In six patients, all radiologic investigations were negative for infarction and in seven patients, CT scans showed new ischemic lesions. In four patients, MR imaging alone showed infarcts, and in four of nine patients who underwent subsequent angiography, acute ischemic findings were demonstrated. Eight patients were treated with volume expansion, eight with full heparinization, and one patient underwent intraarterial thrombolysis. Clinical outcome was excellent or good in 14 of 17 patients, with only three patients (5%) incurring permanent neurologic deficits.CONCLUSION Thromboembolic events related to GDC treatment may be more common than has been reported in the literature. In our experience, this rate was 28%, with persisting deficits in 5%. These events can occur after uncomplicated procedures and may be unaccompanied by radiologic findings. Clinical outcome is usually favorable.